Poseidon and the sea of fury - Holub, Joan (Heroes in training, 2012)
The merciless Cronus and his Titan buddies are in hot pursuit of Zeus, Hera, and Poseidon, who plan to travel across the treacherous boiling sea in order to save a fellow Olympian. They have a boat, but they also have a problem: Poseidon canu2019t swim and is terrified of the water (well, really of the creatures that lurk in its depths). The group faces danger after danger as they battle singing sirens, a fishy and ferocious Titan named Oceanus, and people-eating monsters sent by Cronus himself. Can Poseidon overcome his fears and help his fellow heroes escape Cronus and his cronies?